Left ventricular strain analysis using cardiac magnetic resonance imaging in patients undergoing in‐centre nocturnal haemodialysis. Issue 5 (17th April 2019) - Ong, Jann P; Wald, Ron; Goldstein, Marc B; Leipsic, Jonathon; Kiaii, Mercedeh; Deva, Djeven P; Kirpalani, Anish; Jimenez‐Juan, Laura; Bello, Olugbenga; Azizi, Paymon M; Wald, Rachel M; Wright, Graham A; et al.
ABSTRACT: Aim: Intensified haemodialysis is associated with regression of left ventricular (LV) mass. Compared to LV ejection fraction, LV strain allows more direct assessment of LV function. We sought to assess the impact of in‐centre nocturnal haemodialysis (INHD) on global LV strain (radial, circumferential, and longitudinal) and torsion by cardiac MRI (CMR). Methods: In this prospective, two‐centre cohort study, 37 participants on conventional haemodialysis (CHD, 3–4 h/session for three sessions/week) converted to INHD (7–8 h/session for three sessions/week) and 30 participants continued CHD. Participants underwent CMR using a standardized protocol and had biomarker measurements at baseline and 52 weeks. Results: Among the 55 participants (mean age 55; 40% women) with complete CMR data, those who converted to INHD had a significant improvement in their global circumferential strain (GCS, P  = 0.025), while those continuing CHD did not have any significant changes in LV strain. When the two groups were compared, there was significant improvement in torsion. LV strains were significantly correlated with each other, but not with troponin I, C‐reactive protein, or brain natriuretic protein (NT‐proBNP), except for global longitudinal strain (GLS) with troponin I ( P =  0.001) and NT‐proBNP ( P =  0.038). Conclusion: Conversion to INHD was associated with significant improvement in GCS over one year of study, although comparisons with the CHD group were not significant. There was also a significant decrease in torsion in the INHD group compared with CHD. Improvement in LV regional function would support the notion that INHD has favourable effects on both LV structure and function. Summary A Glance: The use of cardiac MRI is being extended to study myocardial strain patterns in patients on dialysis and supports the utility of MRI in future cardiac imaging‐based outcome studies. This study reports improvement in LV regional function in patients switching to extended in‐centre nocturnal haemodialysis from conventional haemodialysis as compared to those continuing on conventional haemodialysis. Authors report improvement in global circumferential strain and reduced torsion in the extended in‐centre nocturnal haemodialysis group after one year.